(untitled) (Web of Teachers: Inderscience Research, 2024)
This article discusses the benefits of implementing new pedagogical technologies to enhance the teaching and learning process of the Russian language. With the growing need for innovative educational strategies, this paper explores various approaches that modernize Russian language lessons, improve student engagement, and foster linguistic competence. The study examines effective methods, analyzes relevant literature, and provides practical applications of technological tools that support both teachers and students in mastering Russian language skills.